2016
DOI: 10.1111/apha.12686
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between adipokines and myokines in fat browning

Abstract: Skeletal muscle is the largest organ determining whole-body insulin sensitivity and metabolic homoeostasis. Adaptive changes of skeletal muscle in response to physical activity include adjustments in the production and secretion of muscle-derived bioactive factors, known as myokines, such as myostatin, IL-4, IL-6, IL-7 and IL-15, myonectin, follistatin-like 1 or leukaemia inhibitory factor. These myokines not only act locally in the muscle in an autocrine/paracrine manner, but also are released to the bloodstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
128
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(134 citation statements)
references
References 198 publications
(227 reference statements)
3
128
1
2
Order By: Relevance
“…Interestingly, both sympathetic and non-sympathetic pathways (e.g. irisin, BAIBA, IL-6, FGF21, cardiac natriuretic peptides, myostatin, meteorin-like, lactate, and leptin) are sensitive to exercise [6,7]. It was therefore suggested that exercise could be an activator of BAT [6,7,8,9,10,11,12,13].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, both sympathetic and non-sympathetic pathways (e.g. irisin, BAIBA, IL-6, FGF21, cardiac natriuretic peptides, myostatin, meteorin-like, lactate, and leptin) are sensitive to exercise [6,7]. It was therefore suggested that exercise could be an activator of BAT [6,7,8,9,10,11,12,13].…”
mentioning
confidence: 99%
“…It was therefore suggested that exercise could be an activator of BAT [6,7,8,9,10,11,12,13]. Several studies reported that exercise induces beige activation and recruitment in murine models [6,10,11]. In contrast, although available results are not yet conclusive, murine classical BAT seems to be inhibited in response to long-term exercise [10].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Both brown and beige adipocytes have the potential to be metabolically beneficial due to their unique ability to burn excess stored energy and alter the balance between energy intake and energy expenditure. As several excellent reviews have highlighted the importance of white adipose browning in regulating key metabolic aspects that has the potential to combat obesity and related diseases [11], [17], [18], [19], [20], we will briefly examine the emerging role of two key members of the transforming growth factor-β (TGF-β) superfamily, namely myostatin (Mst) and follistatin (Fst).…”
Section: Introductionmentioning
confidence: 99%